Potret Kekerasan dalam Cerpen-cerpen Pilihan Kompas 2010 - Suratno, Pardi (UPA Bahasa Universitas Tidar And HISKI Kedu, 2021)
Violence is a natural condition in a person’s life or society. Everybody, indeed, does not desire violence, however, its occurrence never ends. This article examines violence in short stories selected by Kompas 2010. From the data, there are a number of short stories in the anthology that contains violence, including vigilante violence, medical violence, domestic violence, sexual violence, and cultural violence. “Pengunyah Sirih”, “Ada Cerita di Kedai Tuak Martohap”, “Sunya Ruri”, ”Ordil Jadi Gancan”, “Lebih Kuat dari Mati”, and “Pohon Jejawi” are the short stories contain violence. Text excerpts that contain violence are the data in this research. This research is classified as literature research with a qualitative descriptive framework. The analysis is carried out with an objective literary analysis framework, namely analyzing reality in literary texts autonomously. The results of the study are in the form of conclusions that state that there are variations of violence in the short stories chosen by Kompas 2010, including violence against the law, violence against anarchist demonstrations, domestic violence, sexual violence, medical violence and cultural violence.